2019
DOI: 10.1007/s10570-019-02730-4
|View full text |Cite
|
Sign up to set email alerts
|

Influence of urea on methyl $$\upbeta$$-D-glucopyranoside in alkali at different temperatures

Abstract: The dissolution efficiency plays an important role on the properties of regenerated cellulose-based products. Urea is known to be one of the additives aiding to improve cellulose dissolution in the NaOH(aq) system. The acting mechanism caused by urea has been debated and one of the hypothesis is that urea could induce a conformational change on cellulose, which promotes dissolution. Here we used NMR spectroscopy on a model system for cellulose, namely, methyl $$\upbeta$$β-D-glucopyranoside ($$\upbeta$$β-MeO-Gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Urea is reported to promote reduction in crystallinity and to accumulate on hydrophobic surfaces of drug particles, thereby weakening interactions between hydrophobic particles [53][54][55][56]. Urea may have impacted entropy and shifted the dissolution equilibrium of ACF in buffer as well as water by interacting favorably with drug and SKM [57]. However, higher proportion of urea as in U3 failed to produce expected enhancement.…”
Section: Solubility Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Urea is reported to promote reduction in crystallinity and to accumulate on hydrophobic surfaces of drug particles, thereby weakening interactions between hydrophobic particles [53][54][55][56]. Urea may have impacted entropy and shifted the dissolution equilibrium of ACF in buffer as well as water by interacting favorably with drug and SKM [57]. However, higher proportion of urea as in U3 failed to produce expected enhancement.…”
Section: Solubility Studiesmentioning
confidence: 99%
“…With an aim to achieve still better solubility, superdisintegrant, CP was added in small parts to the binary carrier mixture of SKM and urea. Several studies have reported the use of CP as single carrier component in formulation of SD [34][35][36]57]. Increase in level of CP beyond a threshold value did not produce any further improvement in solubility as observed with C3 and C4, with maximum enhancement being observed with C2 [33][34][35].…”
Section: Solubility Studiesmentioning
confidence: 99%
“…34 Aldehydes are present in the region between 9 and 11 ppm, highlighted in green. The spectra lack features of celluloses and hemicelluloses which are usually found between 2.5-5.5 ppm 35,36 indicating that neither cellulose nor hemicellulose was extracted using MeCN at room temperature (Fig. 5a).…”
Section: Lignin and Extractives In Sawdustmentioning
confidence: 99%